Analisis Produktivitas Pegawai Dalam Pemanfaatan Teknologi Informasi (Studi Kasus: Dinas Pendidikan, Kepemudaan dan Olahraga Kabupaten Badung) - Cahyani, I Gusti Ayu Bintang; Prabawati, Ni Putu Anik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze employee productivity in utilizing technology to enhance task effectiveness at the Department of Education, Youth, and Sports of Badung Regency. The use of information technology in government workplaces is a crucial aspect in supporting performance and achieving organizational goals. This research employs a descriptive qualitative method with a case study approach to provide an in-depth description of employees’ experiences, perceptions, and challenges in integrating technology into daily work processes. Data were collected through in-depth interviews, direct observations, and document analysis. The findings indicate that most employees have utilized technologies such as data processing software, online communication platforms, and internal information systems to support task completion. However, there are still obstacles, including limited training, difficulty adapting to technological changes, and unequal access to digital infrastructure. The study concludes that productivity improvements through technology can be optimized with continuous training, adaptive internal policies, and strengthened digital infrastructure.